Synthesis and Characterization of Schiff Base Complexes of Cobalt(II) - Sheikhshoaie, Iran (Asian Journal of Chemistry, 2010)
Two neutral Co(II) complexes have been synthesized from the Schiff bases derived from salicylaldehyde and n-aminopropane. In this study the syntheses, characterization and some of the theoretical investigations of two Co(II) complexes with two ligands 4-[(4-nitrophenyl)azo]-N-propylamine-salicylaldimine [HL1] and 4-[(4-chlorophenyl)azo]-Npropylamine-salicylaldimine [HL2] have been described. The structures of these compounds have been investigated by their microanalytical, FT-IR, UV-Vis studies. The spectral data of the two Co(II) complexes exhibit square-planar geometry.